HPLC ANALYSIS OF LEAF PROTEIN CONCENTRATE OF BRASSICA OLERACEA VAR. BOTRYTIS - NEHA SAWANT; MEENAKSHI VAIDYA (The Bioscan, 2025)
Protein is a crucial component of a balanced diet, fundamental to maintaining human health. While protein can be obtained from plant and animal sources, underutilized agricultural by-products provide an alternative sustainable protein source. Brassica oleracea var. botrytis (cauliflower) is a widely consumed vegetable in India, yet its leaves, which are rich in essential nutrients, are often discarded as waste. This study explores the extraction of protein from cauliflower leaves using the Leaf Protein Concentrate (LPC) method, followed by amino acid analysis via High-Performance Liquid Chromatography (HPLC). The HPLC results identified 21 amino acids, including essential amino acids such as lysine (0.28%), threonine (0.23%), and methionine (0.15%), along with significant amounts of glutamic acid (1.54%). These findings highlight the potential of cauliflower leaf protein as a sustainable and nutritious dietary supplement, offering a viable strategy for reducing food waste and addressing nutritional deficiencies.